Importance of microRNAs in skin morphogenesis and diseases - Boštjančič, Emanuela (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
MicroRNAs (miRNAs) are small (20-22 nt), non-coding RNAs involved in post-transcriptional gene silencing. Their binding to the 3' UTR of target mRNAs influences the translation or stability of the transcripts. miRNAs havebeen shown to regulate several developmental and physiological processes, including stem cell differentiation and the immune response. Recent findings report their involvement in hair follicle morphogenesis (ablation of miRNAs from keratinocytes causes several defects, such as evagination instead of invagination), in psoriasis (skin-specific expression of miR-203 and psoriasisspecific expression of miR-146a, miR-21 and miR-125b in the skin), inautoimmune diseases affecting the skin, such as SLE and ITP, in wound healing (changes in the expression of specific miRNA at specific phases of theregeneration process), and in skin carcinogenesis (a novel miRNA signature that includes induction of miR-21, a candidate oncogenic miRNA). Researchers worldwide are interested in miRNAs as potential therapeutic targets (such as in the case of psoriasis) and potential diagnostic biomarkers (such as in caseof SLE).
Keywords: Hair Follicle; Kožne novotvorbe; Lasni mešiček; Lupus eritematozni, sistemski; Lupus Erythematosus, Systemic; novotvorbe; Psoriasis; Psoriaza; Rana, celjenje; rane; RNA nizkomolekularna, jedrna; Rna, Small Nuclear; Skin Neoplasms; tumor; Wound Healing